Enzo Collotti e l'Europa del Novecento - Soldani, Simonetta (Biblioteca di storia, 2011)
Emerging from a convention in honour of Enzo Collotti, this book traces his interests and fields of study. These gravitate around the tragic experiences of the Second World War, always played out in a perspective where the horizon is a Europe centred on Germany and on the lacerations that rippled out from Germany itself to embrace the entire continent with the consolidation of Nazism as a totalitarian power grounded in an ideology that was intrinsically reactionary and violently racist. There are six axes of investigation, closely intermeshed, addressed in the various contributions: socialism between the two wars; the lacerations of Germany; the European manifestations of Fascism; the experience of the Shoah, the construction of a shared historic memory of the dramas of the twentieth century and the problems of the Italian "eastern border".